Childhood-Onset Takayasu Arteritis: Clinical Features of Disease and Relapse Risk Factors - Vera Podzolkova; Galina Lyskina; Olga Shpitonkova; Angelina Polyanskaya; Svetlana Chebysheva; Marina Shakhnazarova; Jinbo Zhao; Aleksandr Suvorov; Vera Khudoroshkova; Natalia Geppe (Children)
Background: Takayasu’s arteritis (TA) is a systemic vasculitis that primarily affects the aorta and major arteries. Despite aggressive treatment with glucocorticoids (GCs) and non-biological disease-modifying antirheumatic drugs (nbDMARDs), about 30% of patients experience resistance to therapy or relapse. This study aimed to identify risk factors associated with refractory and relapse TA in pediatric patients. Methods: A retrospective, open-label, case–control study was conducted with 56 pediatric patients with TA diagnosed between February 2011 and October 2022. Fourteen patients were excluded due to insufficient data in their medical records, leaving 42 for further analysis. The patients were divided into two groups: Group 1 (18 patients) with no evidence of relapse and Group 2 (24 patients) with relapse despite first-line treatment at the end of the follow-up period. Clinical, laboratory, and instrumental data were collected and analyzed using R v4.2 and Python v3.10. Results: The median time to relapse was 18 [IQR: 13; -] months according to the Kaplan–Meier curve. Patients with ITAS.A with a diagnosis of TA ≥ 12 had a higher probability of relapse, according to the log-rank criterion (p = 0.006). Symptoms of critical ischemia, such as limb claudication, were more common in Group 2 at diagnosis (p = 0.047), and a trend toward a longer diagnostic delay was observed (p = 0.067). Conclusions: Pediatric patients with an initial ITAS.A score above 12 have a higher risk of relapse when treated with a combination of GCs and nbDMARDs as first-line treatment. Further research is needed to identify high-risk patients more accurately and optimize therapeutic strategies.